THE IMPACT OF THE IMPLEMENTATION OF THE 5E LEARNING CYCLE MODEL ON ARABIC LANGUAGE LEARNING OUTCOMES AT MTS HASYIM ASY’ARI, BATU - Hardy Padmayudha Nugraha; Irza Savita; Qurrotaa'yun Azhari Hamzah; Purnomo Purnomo; Yerry Soepriyanto (STKIP PGRI TULUNGAGUNG, 2025)
This study aims to analyze the effectiveness of the implementation of the 5E Learning Cycle model in improving students’ Arabic language learning outcomes at MTs Hasym Asy’ari, Batu. The research employed a quantitative approach with a pre-experimental one-group pretest-posttest design involving 30 respondents selected through purposive sampling. The pedagogical intervention, comprising the constructivist learning cycle phases (Engagement, Exploration, Explanation, Elabora-tion, and Evaluation), was implemented over an effective period of eight weeks. Descriptive statistical analysis showed an increase in the mean score from 63.87 to 80.17, with a gain score of 16.30. The Shapiro-Wilk normality test confirmed the data followed a normal distribution (p > 0.05), validating the use of parametric statistics. Inferential analy-sis using a paired samples t-test yielded t(29) = 6.004, p < 0.05, indi-cating a statistically significant difference between pre and post interven-tion conditions.